Intrinsic Mechanisms Underlying Hypoxia-Tolerant Mitochondrial Phenotype During Hypoxia-Reoxygenation Stress in a Marine Facultative Anaerobe, the Blue Mussel Mytilus edulis - Sokolov, Eugene P.; Adzigbli, Linda; Markert, Stephanie; Bundgaard, Amanda; Fago, Angela; Becher, Dörte; Hirschfeld, Claudia; Sokolova, Inna M. (Frontiers in Marine Science, 2021)
Hypoxia is common in marine environments and a major stressor for marine organisms inhabiting benthic and intertidal zones. Several studies have explored the responses of these organisms to hypoxic stress at the whole organism level with a focus on energy metabolism and mitochondrial response, but the instrinsic mitochondrial responses that support the organelle’s function under hypoxia and reoxygenation (H/R) stress are not well understood. We studied the effects of acute H/R stress (10 min anoxia followed by 15 min reoxygenation) on mitochondrial respiration, production of reactive oxygen species (ROS) and posttranslational modifications (PTM) of the proteome in a marine facultative anaerobe, the blue mussel Mytilus edulis. The mussels’ mitochondria showed increased OXPHOS respiration and suppressed proton leak resulting in a higher coupling efficiency after H/R stress. ROS production decreased in both the resting (LEAK) and phosphorylating (OXPHOS) state indicating that M. edulis was able to prevent oxidative stress and mitochondrial damage during reoxygenation. Hypoxia did not lead to rearrangement of the mitochondrial supercomplexes but impacted the mitochondrial phosphoproteome including the proteins involved in OXPHOS, amino acid- and fatty acid catabolism, and protein quality control. This study indicates that mussels’ mitochondria possess intrinsic mechanisms (including regulation via reversible protein phosphorylation) that ensure high respiratory flux and mitigate oxidative damage during H/R stress and contribute to the hypoxia-tolerant mitochondrial phenotype of this metabolically plastic species.